Online Learning in Higher Education in the Backdrop of Covid-19: Pakistani Students’ Perspective - Nida Shahzad, Wajeeha Aurangzeb (PJDOL, 2021)
This study explored the students’ perspectives regarding online classes and the problems they have faced while attending online classes during crisis situation of Covid-19. Cconvergent parallel mix method design was adopted for this study and used online survey and structured interviews for data collection. The participants of the study were first semester social sciences students from two public universities of Rawalpindi city. Sample size for the survey was n=100 which was selected purposively and conveniently whereas, sample size for structured interviews was n=12.